2022
DOI: 10.21203/rs.3.rs-1807001/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Datura Stramonium leaves extract Silver Nanoparticles regulates PINK1 gene in Parkinson’s disease model of Drosophila melanogaster

Abstract: In recent years, several eco-friendly processes for the synthesis of silver nanoparticles (AgNPs) are increasing; they have tremendous applications in the field of diagnosis and therapeutic values for various diseases /disorders. In this article the green synthesis of Datura stramonium leaves extract silver nanoparticles (DS-AgNPs) was carried out and are characterized for different properties like reduction of Ag + to Ag◦, absorption maxima, functional group of secondary metabolites, crystalline structure, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…This finding is supported by a prior study that revealed that plant constituents dramatically increased cell viability. Due to the activation of antioxidant defense systems or the existence of bioactive components that quench free radicals, UD-AgNPs have protective properties [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is supported by a prior study that revealed that plant constituents dramatically increased cell viability. Due to the activation of antioxidant defense systems or the existence of bioactive components that quench free radicals, UD-AgNPs have protective properties [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…An early-onset variant of autosomal recessive Parkinson’s disease is caused by mutations in the PINK1 gene ( Deas et al, 2009 ). In a study by Shivanna et al (2022) , it was discovered that AgNPs made from Datura stramonium leaf extract of spherical shape and 39–59 nm size have the power to alter the regulation of the PINK1 gene. It was found that after being fed with the AgNPs, the flies had higher geotaxis behavior and a consequently favorable survival percentage in the investigation, which was conducted in vivo on a mutant Parkinson’s Disease model of Drosophila melanogaster .…”
Section: Medicinal Properties Of Silver Nanoparticlesmentioning
confidence: 99%